Large Tunable 16-Tupled Millimeter Wave Generation Utilizing Optical Carrier Suppression With a Tunable Sideband Suppression Ratio - Asha; Dahiya, Sandeep (Frontiers in Physics, 2021)
Coping up with the rising bandwidth demands for 5G ultra high speed applications, utilizing Millimeter ((MM) wave spectrum for data transmission over the radio over fiber based system is the ideal approach. In this paper, a highly conversant and spectrally pure photonic generation of a 16-tupled MM wave signal using series connected DD-MZM with lower modulation index, splitting ratio and wider tunable range is presented. A 160 GHz MM wave is generated through double sideband optical carrier suppression technique having optical sideband suppression ratio (OSSR) of 69 dB and radio frequency sideband suppression ratio (RSSR) of 40 dB. However, OSSR and RSSR are tunable with values greater than 15 dB when modulation index (M.I.) varies from 2.778 to 2.873, ± 8˚ phase drift and a 15 dB enhancement in OSSR with a wider non-ideal parameter variation range giving acceptable performance can be seen in the model as compared with previous researches.